2021
DOI: 10.1186/s12882-021-02362-6
|View full text |Cite
|
Sign up to set email alerts
|

CB1 receptor antagonist rimonabant protects against chronic intermittent hypoxia-induced renal injury in rats

Abstract: Background Obstructive sleep apnoea (OSA) induced chronic kidney disease is mainly caused by chronic intermittent hypoxia (CIH). Our study investigate the mechanism underlying CIH-induced renal damage and whether the cannabinoid receptor 1 (CB1R) antagonist rimonabant (Ri) alleviates CIH-induced renal injury. Methods Male Sprague-Dawley rats were randomly divided into five groups: one normal control (NC) group, two chronic intermittent hypoxia (CIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Long-term moderate-to-severe IH (20 to 60 cycles/h. 21–8% O 2 , 35–60 days) induces kidney histological changes [ 64 , 65 ]; increases markers of fibrosis [ 5 , 6 , 65 ], inflammation [ 5 , 6 , 66 , 67 ], oxidative stress [ 3 , 5 , 6 , 66 ], and ER stress [ 3 ]; promotes abnormal mitochondrial dynamics [ 68 ] and cell apoptosis [ 3 , 5 , 6 , 64 , 67 ]; increases growth factors [ 64 ], noradrenaline [ 65 ] and Ang II concentrations [ 6 ]; stabilizes Hif1α [ 5 ] and increases serum Cr and blood urea nitrogen (BUN) levels [ 67 ] and albuminuria [ 64 ]. It is important to note that the aforementioned studies were performed in long-term moderate and severe IH rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term moderate-to-severe IH (20 to 60 cycles/h. 21–8% O 2 , 35–60 days) induces kidney histological changes [ 64 , 65 ]; increases markers of fibrosis [ 5 , 6 , 65 ], inflammation [ 5 , 6 , 66 , 67 ], oxidative stress [ 3 , 5 , 6 , 66 ], and ER stress [ 3 ]; promotes abnormal mitochondrial dynamics [ 68 ] and cell apoptosis [ 3 , 5 , 6 , 64 , 67 ]; increases growth factors [ 64 ], noradrenaline [ 65 ] and Ang II concentrations [ 6 ]; stabilizes Hif1α [ 5 ] and increases serum Cr and blood urea nitrogen (BUN) levels [ 67 ] and albuminuria [ 64 ]. It is important to note that the aforementioned studies were performed in long-term moderate and severe IH rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent hypoxia (IH), one of the novel pathophysiological characteristics of OSA, can result in several physiological changes, including systemic inflammation, endothelial dysfunction, oxidative stress, and apoptosis. Experimental studies proved that IH causes renal damage, inducing high renal oxidative stress [ 7 ] and apoptosis levels [ 8 10 ], and abnormal mitochondrial dynamics [ 11 ]. Consistent with previous studies, a study by our team confirmed that chronic IH contributed to high protein levels associated with autophagy and apoptosis in mice mimicking OSA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was briefly approved as an antiobesity medication, but it was withdrawn due to serious side effects, including psychosis. Currently, this active compound has only experimental application [108].…”
Section: Of 36mentioning
confidence: 99%